2017
DOI: 10.1111/jch.13028
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the optimal method of blood pressure measurement for limited‐resource rural communities in the “Community Health Assessment Program—Philippines”

Abstract: The Community Health Assessment Program-Philippines (CHAP-P) is an international collaboration of investigators whose aim is to adapt a previously proven Canadian community-based cardiovascular awareness and prevention intervention to the Philippines and other low-middle-income countries. Choosing a method of blood pressure measurement for the research program presents a challenge. There is increasing consensus globally that blood pressure measurement with automated devices is preferred. Recommendations from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…2 In addition, several studies [5][6][7] have demonstrated that uAOBP predicts target organ damage, as well as ambulatory BP (ABP) measurement, which is considered the reference standard for BP measurement. 8 Despite increasing adoption of uAOBP, [9][10][11] no studies examining its utility as a screening tool for hypertension have been conducted to date, leading to some confusion on how to incorporate uAOBP in the diagnosis of hypertension. 12 While there are data comparing uAOBP to ABP monitoring (ABPM), these have been conducted among high cardiovascular risk individuals, the majority of whom were already on treatment for hypertension.…”
mentioning
confidence: 99%
“…2 In addition, several studies [5][6][7] have demonstrated that uAOBP predicts target organ damage, as well as ambulatory BP (ABP) measurement, which is considered the reference standard for BP measurement. 8 Despite increasing adoption of uAOBP, [9][10][11] no studies examining its utility as a screening tool for hypertension have been conducted to date, leading to some confusion on how to incorporate uAOBP in the diagnosis of hypertension. 12 While there are data comparing uAOBP to ABP monitoring (ABPM), these have been conducted among high cardiovascular risk individuals, the majority of whom were already on treatment for hypertension.…”
mentioning
confidence: 99%
“…The questions include: demographics; knowledge about diabetes and cardiovascular health; risk factors and behaviours, including the Finnish Diabetes Risk Calculator (FINDRISC) [23]; quality of life using the EQ-5D-5 L [24, 25]; perceived confidence; perceived concern and understanding of risk; self-efficacy to improve health behaviours; physical activity using the International Physical Activity Questionnaire (IPAQ) [22]; and health utilization and access. The WatchBP Office Target will be used to measure blood pressure as it was found to show the most reliable results based on our pilot study [27]. This community survey will be completed at baseline and at 6 months and will use an open-cohort design.…”
Section: Methodsmentioning
confidence: 99%
“…When compared with graduates of the conventional medical curriculum, a study has shown that ADZU-SOM graduates were more likely to work as government physicians than in private health facilities and as generalists than specialists [20]. Although lessons from the ADZU-SOM experience were previously described in the literature [15][16][17][18][19][20][21][22][23][24][25][26][27][28], none has explored how primary care and public health could be integrated during medical students' training based on social accountability and CEME. Since there are calls to integrate primary care and public health for optimal health systems [29], more evidence is needed about how the functions could come together in practice to achieve potential synergies for enhancing individual-and population-level health [30].…”
Section: Introductionmentioning
confidence: 99%